The latitudinal gradient in dispersal constraints: Ecological specialisation drives diversification in tropical birds - Salisbury, C; Seddon, N; Cooney, C; Tobias, J (2012)
Physiological and behavioural constraints arising from ecological specialisation are proposed to limit gene flow and promote diversification in tropical lineages. In this study, we use phylogenetic analyses to test this idea in 739 Amazonian bird species. We show that patterns of species and subspecies richness are best predicted by a suite of avian specialisms common in tropical avifaunas but rare in the temperate zone. However, this only applied to niche traits associated with dispersal limitation rather than vagility. These findings are consistent with the view that diversity is promoted by more finely partitioned niches, although not simply by coevolutionary adaptation and niche packing as is often assumed. Instead, they suggest that diversification is driven by dispersal constraints, and that niches characterised by these constraints are biased towards tropical systems. We conclude that specialised tropical niches reduce the likelihood of dispersal across barriers, thereby increasing allopatric diversification and contributing to the latitudinal diversity gradient. © 2012 Blackwell Publishing Ltd/CNRS.